Accounting abuse - Bartoňová, Tereza (2018)
The thesis "Abuse accounting" have focused on the basic definitions of the creative accounting and deception, categorizing and methods of implementation. The following chapters are directed to the field of economic crime, the most common description of the perpetrators of this illegal activity and comparing forensic investigation and auditing.In conclusion, the thesis is plunging attention to practical examples of abuse accounts both worldwide and in the Czech Republic.